Analysis of student support activities at school in terms of extroverted and introverted personalities - Siska Anita; Suci Damayanti; Rahma Indah Sari; Rodinatul Munawaroh; Jailani, Munawar (International journal of education and teaching zone, 2023)
This study aims to analyze extroverted and introverted students using descriptive qualitative methods. Subject research was conducted with students in  SMPN 12 Sarolangun. The population of the object is in the form of counseling guidance teachers, as many as 152 people, and students. The research sample used is in the form of whole students with total sampling techniques. This research collects data through a questionnaire given to students with 15 questions, 6 for extrovert students and 9 for introvert students. Data was analyzed from the questionnaire results to determine which students are extroverted or introverted. The calculation is that each question is 100 points multiplied by The number of students who voted yes and divided by the overall number of students. From the data, The results of the study were known to 14 (26.92%) introverted students and 38 (73.08%) extroverted students.